2011
DOI: 10.1038/oby.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Suppression of Hunger by a Specific Alginate in a Low‐Viscosity Drink Formulation

Abstract: Addition of specific types of alginates to drinks can enhance postmeal suppression of hunger, by forming strong gastric gels in the presence of calcium. However, some recent studies have not demonstrated an effect of alginate/calcium on appetite, perhaps because the selected alginates do not produce sufficiently strong gels or because the alginates were not sufficiently hydrated when consumed. Therefore, the objective of the study was to test effects on appetite of a strongly gelling and fully hydrated alginat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 31 publications
(69 reference statements)
1
36
0
Order By: Relevance
“…In addition, it is used as a food additive (thickening stabilizer) and medicinal additive. [17][18][19][20] However, excessive intake of sodium is one of the risk factors for hypertension. 21) Therefore, if the calcium salt of alginic acid (Ca-Alg) has a similar effect of Na-Alg, it might be more beneficial than Na-Alg.…”
mentioning
confidence: 99%
“…In addition, it is used as a food additive (thickening stabilizer) and medicinal additive. [17][18][19][20] However, excessive intake of sodium is one of the risk factors for hypertension. 21) Therefore, if the calcium salt of alginic acid (Ca-Alg) has a similar effect of Na-Alg, it might be more beneficial than Na-Alg.…”
mentioning
confidence: 99%
“…[13][14][15] It also protects the gastric mucous membrane. 16) Moreover, it was reported that accumulation of strontium (Sr) in the human body decreased when sodium alginate (Na-Alg) was ingested before exposure to Sr. 17) Further, when rats pre-fed with NaAlg for ten days were administered Sr, the cumulative amount of Sr in the body was markedly reduced, compared with the control group.…”
mentioning
confidence: 99%
“…[3][4][5] Alginate (ALA), an intercellular polysaccharide associated with brown algae, is used as a food additive and as a health food to decrease blood cholesterol and inhibit weight gain. 3,[6][7][8] It also has a protective effect on the gastric mucous membrane. 9) Further, it has already been reported that accumulation of strontium (Sr) in the human body decreased to one-eighth when sodium alginate (ALA-Na) was ingested before administration of Sr. 10) Moreover, when rats pre-fed with ALA-Na for ten days were administered radioactive Sr ( 85 Sr, half-life= 64.8 d), the cumulative amount of 85 Sr in the body was markedly reduced, compared with the control group.…”
mentioning
confidence: 99%